2022
DOI: 10.1111/cns.13936
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of different tirofiban administration routes on acute ischemic stroke patients with successful recanalization: A propensity score matching analysis

Abstract: Objective This study aimed to explore the effect of different administration routes of a low dose of tirofiban on acute ischemic stroke (AIS) patients with successful recanalization after endovascular treatment (EVT). Methods This is a cohort study that retrospectively analyzed data of patients with AIS who underwent EVT and achieved successful recanalization from a prospective registry. Eligible patients were divided into three groups according to their use of tirofiban. Propensity score matching (PSM) was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
4
6
1
Order By: Relevance
“… 24 A full dose of intraarterial tirofiban (10 μg/kg) followed by continuous intravenous tirofiban led to a higher hemorrhagic risk compared with a full dose of intravenous tirofiban or no tirofiban, while a low dose of intraarterial+intravenous tirofiban improved the outcomes of patients with anterior circulation stroke after EVT. 11 , 16 The dose of tirofiban in this study was also relatively low, which was approximately identical to that in the study by Guo et al and assured the safety of the current dosing regimen of tirofiban. 16 …”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“… 24 A full dose of intraarterial tirofiban (10 μg/kg) followed by continuous intravenous tirofiban led to a higher hemorrhagic risk compared with a full dose of intravenous tirofiban or no tirofiban, while a low dose of intraarterial+intravenous tirofiban improved the outcomes of patients with anterior circulation stroke after EVT. 11 , 16 The dose of tirofiban in this study was also relatively low, which was approximately identical to that in the study by Guo et al and assured the safety of the current dosing regimen of tirofiban. 16 …”
Section: Discussionsupporting
confidence: 82%
“… 20 However, most of these studies did not report detailed information about the dose or the duration of intraarterial tirofiban in their cohorts. 16 , 19 , 20 A recent study from Guo et al illustrated that half of the patients receiving intravenous tirofiban were also treated with intraarterial local tirofiban in clinical practice in China, and simultaneous intraarterial+intravenous tirofiban rather than intravenous tirofiban improved outcomes of patients with anterior circulation stroke. 16 In our preceding RESCUE‐BT trial, we found that intravenous tirofiban preceding thrombectomy failed to improve the clinical outcomes of patients with anterior circulation stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of platelet aggregation blockade of tirofiban is dose‐dependent and can be rapidly reversible in 1.5–2.2 h 12 . Several studies have evaluated the efficacy of tirofiban in patients receiving EVT 13,14 . However, fewer studies have focused on the factors affecting the outcomes of the EVT followed by tirofiban in AIS patients.…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 The effect of platelet aggregation blockade of tirofiban is dose‐dependent and can be rapidly reversible in 1.5–2.2 h. 12 Several studies have evaluated the efficacy of tirofiban in patients receiving EVT. 13 , 14 However, fewer studies have focused on the factors affecting the outcomes of the EVT followed by tirofiban in AIS patients. In this study, we performed exploratory analyses regarding factors influencing functional outcomes in AIS patients who received adding tirofiban to EVT.…”
Section: Introductionmentioning
confidence: 99%